Selfheal Stable Routing Protocol for Ad-hoc Network - Pawar, Rosy; Kush, Ashwani (International Journal of Computer Sciences and Engineering, 2025)
Wireless networking is a new emerging era. It has potential applications in extremely unpredictable and dynamic environments. Individuals and industries choose wireless because it allows flex¬ibility of location, whether that means mobility, portability, or just ease of installation at a fixed point. In mobile ad-hoc network, mobile nodes are continuously moving from one location to another. Thus, MANET topology can change often and unpredictably. Mobility of nodes is one of the major issue of concern in mobile Ad- hoc network because it causes a link failure. In this paper, a new scheme has been suggested which would help mobile nodes to maintain routes to destination with more stable route selection. This makes route maintenance and recovery phase more efficient and fast. The performance of the proposed routing protocol named as Selfheal Stable Routing protocol (SSRP) is evaluated some major performance metrics which include Packet Delivery Ratio, throughput and End to End Delay. The study is based on simulation runs adopting CBR traffic pattern taking care of node failure scenarios.